2011
DOI: 10.1364/boe.2.000243
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of airway thickness changes in smoke-inhalation injury using in-vivo 3-D endoscopic frequency-domain optical coherence tomography

Abstract: Smoke inhalation injury is frequently accompanied by cyanide poisoning that may result in substantial morbidity and mortality, and methods are needed to quantitatively determine extent of airway injury. We utilized a 3-D endoscopic frequency-domain optical coherence tomography (FD-OCT) constructed with a swept-source laser to investigate morphological airway changes following smoke and cyanide exposure in rabbits. The thickness of the mucosal area between the epithelium and cartilage in the airway was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…The airway wall segmentation and measurement methods have been described in detail (31); similar software-based airway tissue measurement has been validated in previous OCT studies (12)(13)(14)(15)(16)(17). A single optimal data set from each LR-OCT case was selected based on signal-to-noise ratio, clarity of tissue contours, and soft tissue substructural resolution.…”
Section: Image Segmentation and Micrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The airway wall segmentation and measurement methods have been described in detail (31); similar software-based airway tissue measurement has been validated in previous OCT studies (12)(13)(14)(15)(16)(17). A single optimal data set from each LR-OCT case was selected based on signal-to-noise ratio, clarity of tissue contours, and soft tissue substructural resolution.…”
Section: Image Segmentation and Micrometrymentioning
confidence: 99%
“…OCT evaluation and measurement of airway wall microanatomy has been validated with comparative computed ORIGINAL ARTICLE tomography (12) and histology (13)(14)(15)(16)(17). Previous reports describe OCT imaging of postintubation subglottic injury in ex vivo animal models (17,18) and intubated neonates (19).…”
mentioning
confidence: 99%
“…Increased thickening of basement membrane according to the epithelial thickening was apparent with following OCT monitoring. In several studies, the extent of injury has been quantitatively measured with this spectral-domain OCT system [13][14][15]. In this study, we first measured thickness of the basement membrane in injured tracheas.…”
Section: Discussionmentioning
confidence: 99%
“…As a nonionizing, non-invasive medical imaging modality, optical coherence tomography (OCT) has been used to perform high resolution, cross-sectional imaging of biological tissues. Previous studies [6][7][8][9][10][11] have demonstrated the flexibility of OCT to image the airways of different animals in vivo. Among them, the Fourier domain long-range swept source OCT (LR-SSOCT) exhibits higher sensitivity, faster imaging speed and an extended imaging range compared to conventional OCT systems.…”
Section: Introductionmentioning
confidence: 99%